Effect of elevated CO2 concentration and temperature on antioxidant capabilities of multiple generations of Bemisia tabaci MEAM1 (Hemiptera: Aleyrodidae). (November 2017) - Li, Ning; Li, Yaohua; Zhang, Shize; Fan, Yongliang; Liu, Tongxian
Graphical abstract: Highlights: Elevated [CO2 ] and temperature on Bemisia tabaci physiology were examined. The antioxidant capabilities showed differences during different treatments. The antioxidant capabilities showed differences across different generations. [CO2 ], temperature and generation had an interactive effect. The acclimation or adaptation may have occurred. Abstract: A rise in atmospheric carbon dioxide concentration ([CO2 ]) and a warming climate are two of the most conspicuous characteristics of global climate change in this century. However, studies addressing the combined impact of rising [CO2 ] and temperature on herbivore insect physiology are still limited. In this study we investigated the combined effects of elevated [CO2 ] and temperature on major antioxidative enzymes, including superoxide dismutase (SOD), catalase (CAT), peroxidases (POD) and detoxification enzymes of glutathione-S-transferases (GST) and acetylcholinesterase (AChE) in three consecutive generations of Bemisia tabaci Middle East-Asia Minor 1 (MEAM1, commonly known as B biotype) adults. The results indicated that the antioxidant capabilities of B. tabaci differed significantly during different treatments across different generations. Elevated [CO2 ] markedly increased POD, GST and AChE activities in the first generation, and SOD, CAT and GST activities in the second generation, but reduced POD activity in the third generation at ambient temperature. Under elevated temperature, elevated [CO2 ] significantly increased GST and AChE activities in the first generation and CAT activity in the third generation, reduced SOD activity in the third generation and reduced AChE activity in the second generation. [CO2 ], temperature and insect generation interacted to affect the antioxidant capabilities of B. tabaci . These results suggest both that changes in antioxidant capabilities vary in response to either [CO2 ] or temperature, or a combination of both, leading to oxidative stress and also that antioxidant enzymes play important roles in reducing oxidative damage in B. tabaci . Changes in the exposure of antioxidant compounds over the course of three generations suggest that acclimation and/or adaptation to elevated [CO2 ] and temperature may have occurred. This study represents the first comprehensive report on the antioxidant defense mechanism in successive multiple generations of an insect species under combined elevated [CO2 ] and temperature levels. These results offer further insights into the effects of elevated [CO2 ] and temperature on different generations of insect herbivores and provide more detailed information for population predictions.